2008
DOI: 10.1007/s10995-008-0423-4
|View full text |Cite
|
Sign up to set email alerts
|

The Agency for Healthcare Research and Quality’s Children’s Health Research Portfolio

Abstract: The objective of this work was to describe and assess the potential impact of the Agency for Healthcare Research and Quality's, AHRQ's, children's health activities. Using AHRQ databases and publications lists and generic search engines, we developed a comprehensive list of AHRQ's funded children's health activities (1990-2005) and related publications (1996-2002). We conducted bibliometric analyses and used Stryer's (2000) approach to categorize their potential impact. We found that AHRQ's child health portfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Similarly, in 2 previous studies women who received fertility treatments were less likely to be active in early pregnancy. 16,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in 2 previous studies women who received fertility treatments were less likely to be active in early pregnancy. 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, among active women, the intensity and duration of recreational activity tend to decline during pregnancy. 4-17 Low levels of physical activity may lead to higher weight gain, 18 and excess weight gain during pregnancy may be related to higher body mass index in the long term, even 15 years later. 19 To design and target interventions for maintaining or safely increasing activity during pregnancy, it is useful to understand factors that are correlated with physical activity during pregnancy.…”
mentioning
confidence: 99%
“…However, similar to other types of female migration, they may experience downward social mobility and are vulnerable to disempowerment in the migration processes (Piper 2004, Hugo 2000). To date, the limited research on the health of transnational marriage migrants has focused primarily on reproductive health issues (Xirasagar et al 2010, Hsieh et al 2011) and their vulnerabilities to social isolation, physical abuse and mental distress (Choi, Cheung, and Cheung 2012, Williams and Yu 2006, Choi et al 2012). In this article, we examine the link between the migration processes and self-rated health among transnational marriage migrants in South Korea, a gendered migration flow at a new immigrant destination.…”
Section: Introductionmentioning
confidence: 99%
“…In recent reviews, Alio et al suggested that paternal involvement is beneficial for reducing infant mortality (Alio et al 2010; Alio et al 2009). The amount of paternal involvement before birth is partially associated with the relationship status of the mother and father (Alio et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggested that cohabitation was a determinant of adverse birth outcomes such as low birth weight and infant mortality (Luo et al 2004), and the infants born to parents in cohabiting unions received less social support and paternal involvement than infants born to married parents (Alio et al 2010; Alio et al 2009). Therefore, we hypothesized that cohabitation was positively associated with infant deaths.…”
Section: Introductionmentioning
confidence: 99%